Influence of silver nanoparticles on heavy metals of pore water in contaminated river sediments. (November 2016) - Tao, Wei; Chen, Guiqiu; Zeng, Guangming; Yan, Ming; Chen, Anwei; Guo, Zhi; Huang, Zhenzhen; He, Kai; Hu, Liang; Wang, Lichao
Abstract: Despite the increasing knowledge on the discharge of silver nanoparticles (AgNPs) into the environment and their potential toxicity to microorganisms, the interaction of AgNPs with heavy metals remains poorly understood. This study focused on the effect of AgNPs on heavy metal concentration and form in sediment contaminated with heavy metals from the Xiangjiang River. The results showed that the concentration of Cu, Zn, Pb and Cd decreased and then increased with a change in form. The changes in form and concentrations of heavy metals in pore water suggested that Cu and Zn were more likely to be affected compared to Pb and Cd. The concentrations of Hg in sediment pore water in three AgNPs-dosed containers, increased greatly until they reached their peaks at 4.468 ± 0.133, 4.589 ± 0.235, and 5.083 ± 0.084 μg L −1 in Bare AgNPs, Citrate AgNPs and Tween 80 AgNPs, respectively. The measurements of Hg concentrations in the sediment pore water, combined with SEM and EDX analysis, demonstrated that added AgNPs stabilized in pore water and formed an amalgam with Hg 0, which can affect Hg transportation over long distance. Graphical abstract: Highlights: AgNPs caused heavy metals to be transferred from surface water to sediment. Heavy metals were released to water phase in ionic form after sedimentation. Hg 2+ was reduced to Hg 0 and formed Ag-Hg amalgam in sediment pore water.